THE EXTENT TO WHICH TEACHERS OF TALENTED AND CREATIVE STUDENT POSSES KNOWLEDGE AND SKILLS ACCORDING TO CEC-NAGC CRITERIA IN JORDAN - Alshurman, Wael Mohammad; Alkhateeb, Akef Abdallah (European Scientific Journal, ESJ, 2015)
The aim of this study is to identify the extent to which teachers of talented and creative students possess knowledge and skills according to CEC- NAGC criteria in Jordan. The study was carried out on a sample of (36) teachers at king Abdullah II challenging school at Irbid and Mafraq governorates during the 2014/2015 school year in Jordan. Means, standard deviation, and MANOVA were employed in answering the research questions. Results showed that the extent to which teachers of gifted and creative students possess knowledge and skills of Foundations, Development and Characteristics of Learners, Individual Learning Differences, Instructional Strategies, learning environment and social interactions, assessment, Professional and Ethical Practice, and Collaboration was moderate. On the other hand, the extent to which these teachers possess knowledge, skills of language, communication skills, and Instructional planning was high. Results also showed no statistically significant differences in the degree to which these teachers possess knowledge and skills according to CEC- NAGC criteria. Thus, this is due to the subjects of educational qualification, teaching experience, and specialization from the educational supervisor’s point of view. These differences were found in the degree to which respondents possess these knowledge and skills according to CEC- NAGC criteria due to their sex. Thus, this criteria was found from an educational supervisor’s point of view. Results also showed the need for finding programs that are prepared and specialized in preparing teachers of talented and creative students. It provides them with a pre service according to CEC- NAGC criteria. In addition, it shows the need to force talented student’s teachers to obtain the certificate for teaching talented students according to these criteria.